PENGEMBANGAN MANAJEMEN DAYA TARIK WISATA BERBASIS QUALITY EXPERIENCES DI OBJEK WISATA ALAS KEDATON TABANAN - Indrawati, Yayu; Sudana, I P.; Mahadewi, N P. Eka; Mananda, IG.B. Sastrawan; Ariani, N M. (Buletin Udayana Mengabdi; Vol 12 No 2 (2013): Volume 12 No.2 – September 2013, 2013)
In the recent days, to understanding the consumers behaviour is becoming a primary concern in marketing. This is also including in tourism marketing particularly tourism destination. The phenomenon of understanding the consumer taste in tourism is popularly known as quality experience. It has a meaning that when tourist spends their money on a certain destination they expect for quality experience. It can be seen on their satisfaction that appear on their willingness to revisit or giving the positive impression to their friends and relatives. Today, there is a downward point in tourist destination in the last five years. Previously there were 1500 visitors per day, but lately it is only 10.000 both for international and domestic visitors. It is caused by the raise of competitor’s number and the tourist responses towards Alas Kedaton site. Such impression comes from its cleanliness, the hospitality of the staff, the price of entrance fee, and lack of facilities. Other instances are the uncomfortable way to get to the site, as well as the absence of spiritual facilities for Muslim visitors for praying during their visit to this place.